Penilaian Kinerja Berbasis Rasio Keuangan Pada PT. Bank Mandiri (Persero) Tbk Tahun 2020 – 2022 - Nurul Azmi; Grace Cleosa Panesa Pelmelay (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine and analyze the financial performance of PT. Bank Mandiri (Persero) Tbk uses liquidity, solvency and profitability ratios measured by industry standards. The analytical method used in this research is descriptive quantitative. The data source in this research is the annual financial report of PT. Bank Mandiri (Persero) Tbk during 2020-2022. The research results show that the overall analysis of the average value of the current ratio and quick ratio shows that the condition is not good because the ratio is below industry standards, namely 200% and 150%. For analysis of the average value of the Debt to Equity Ratio, it shows that the condition is not good because the ratio is above the industry standard of 90%. Meanwhile, the Debt to Assets Ratio shows good condition because the ratio is below the industry standard of 35%. For the analysis of the average ROA and ROE, the results are not good because the ratio is below the industry standard, namely 30% and 40%. Meanwhile, ROI shows good results because the ratio is above the industry standard, namely 30%.